Pola Penggunaan Media Sosial Whatsapp dalam Pemenuhan Informasi Mahasiswa Universitas Terbuka Mataram - Prihandoyo Prihandoyo; Sudarwo Sudarwo (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to identify and analyze WhatsApp social media usage patterns in fulfilling information on Mataram Open University students. The method used in this research is a descriptive correlational survey. The results of this study are 1. The frequency and time spent by respondents in finding information in the WhatsApp community are high. The types of information most sought by respondents were tutorials and grades. ICT ownership factors and information-seeking motives have an authentic relationship with WhatsApp community usage patterns. In contrast, the sexes, age, occupations, and information most sought after do not have a real relationship. 2. The level of fulfillment of student information needs through the WhatsApp community is high. Factor patterns of use of the WhatsApp community, such as the number of visit days, the number of visits, and the amount of visit time, have an authentic relationship with the level of student information fulfillment. Keywords: usage patterns, information, communication, WhatsApp social media